TEACHING SKILLS OF THE TEACHING STAFF AT THE COLLEGE OF AGRICULTURE AND FORESTY , MOSUL UNIVERSITY FROM THE STUDENTS POINTS VIEW. - Ibrahim, Dhuwayyah Ahmed; Idriss, Luma Monther (Diyala Agricultural Sciences Journal, 2011)
The current study aims at identifying the level of the teaching skills of the teaching staff at the college of Agriculture and Forestry, Mosul University according to the students' points of view as well as the extent of practicing the teaching skills by the teaching staff and arranging the domains of the research according to the level of the practice. In order to obtain the relevant data, a two-parts questionnaire was used: the first part is related to the sample data, while the second part included a group of items (30 items) to measure the lecturers' levels of practice and these were distributed to include planning, executing and evaluation. After verifying the apparent validity of the questionnaire, consistency was measured using the half partitioning method. The study included the fourth grade students of college of Agriculture and Forestry, Mosul University for the academic year (2008-2009). The number of the students was (318) male and female students distributed on all the department of the college (10 departments). A random sample of the number of the students was (144) male and female students was taken (50% of the population). The results showed that (43%) of the subjects were of high level of teaching practice, (40%) were of middle teaching practice and (15%) were of low level of practice and this indicates that the result is fairly good. Also, results showed that the five first skills were of high degrees and according to the following arrangement: (presenting the lecture in details, relating the theoretical aspects with the practical ones, building good relationships with the students based on understanding and mutual respect, taking a good care of the logical sequence of the scientific subject and pointing out the objectives of the subject he/she is teaching). For the skills that came in the last positions, the degree of practice was weak and the sequence was as follows: (presenting demonstrating films to the students, presenting the lecture in different steps, making an evaluation to the students after the end of each lecture, developing the feedback continuously and keeping up with the recent teaching aids). The researcher would recommend that the authorized departments at the University should continue in developing the skills of the teaching staff by making the teaching staff use and adopt teaching skills in order to get better results and also this study should be conducted in other university in Iraq for the same fields or conducting similar studies for other fields also.